Essentials of pediatric nutrition - Samour, Patricia Queen; King, Kathy (Jones & Bartlett Learning, 2013)
Essentials of Pediatric Nutrition relays the key information needed to work in pediatric nutrition with various age groups and diseases/conditions. This consolidated and modified version of the very successful fourth edition of Pediatric Nutrition covers the core best-practice guidelines on the most vital information concerning the normal child from preconception through adolescence as well as infants and children with diseases/conditions affecting nutritional status. It provides the tools and resources needed to assess, monitor, and determine appropriate interventions aimed at maximal nutrition status and growth. Topics covered: Recommended weight gain and key nutrient concerns during pregnancy Nutrition screening and assessment Unique nutrient concerns and management considerations of high risk neonates Food hypersensitivities Unique nutritional challenges of infants and children with disabilities Diabetes Common types of cancers (such as leukemia) in infants and children and their treatment challenges Enteral and/or parenteral nutrition Approved botanicals in pediatric practice.